1964
DOI: 10.2307/1937113
|View full text |Cite
|
Sign up to set email alerts
|

Use of Life Tables in a Bioclimatic Study of an Experimental Aphid‐Braconid Wasp Host‐Parasite System

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on TueHOST-PARASITE LIFE TABLES 119 to environmental extremes of drought and flash floods. 2. The natural life span for most Rhinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
2

Year Published

1971
1971
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 15 publications
4
86
0
2
Order By: Relevance
“…The rates and patterns of oviposition recorded for P. volucre parasitizing M. euphorbiae are similar to those reported by Messenger (1964) for Praon palitans Muesebeck (Hymenoptera: Braconidae: Aphidiinae) parasitizing Therioaphis trifolii form maculata (Buckton) (Hemiptera: Aphididae). Both parasitoids oviposit for periods exceeding 15 days and approximately 50% of the eggs are laid within the first four days of a female's life.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The rates and patterns of oviposition recorded for P. volucre parasitizing M. euphorbiae are similar to those reported by Messenger (1964) for Praon palitans Muesebeck (Hymenoptera: Braconidae: Aphidiinae) parasitizing Therioaphis trifolii form maculata (Buckton) (Hemiptera: Aphididae). Both parasitoids oviposit for periods exceeding 15 days and approximately 50% of the eggs are laid within the first four days of a female's life.…”
Section: Discussionsupporting
confidence: 83%
“…Both parasitoids oviposit for periods exceeding 15 days and approximately 50% of the eggs are laid within the first four days of a female's life. However, P. volucre has a higher total fertility (504 eggs) than P. palitans (298.8 eggs;Messenger, 1964). In other Aphidiinae, such as A. colemani and Lysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae: Aphidiinae), about 85-90% of the offspring is produced during the first three days after female emergence and females oviposit for an average of 8 days (Rodrigues et al, 2003;Torres et al, 2007;Silva et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Blue alfalfa aphid was most abundant during late winter -early spring, while pea aphid and spotted alfalfa aphid populations increased only during late summer -early fall. Numerous studies have shown that pea aphid, in contrast to spotted alfalfa aphid, does not do well during the hot summer in the San Joaquin Valley, where daily temperatures often exceed 40°C (Messenger 1964;Gutierrez and van den Bosch 1970). Blue alfalfa aphid would likewise be expected to perform poorly in this area, as its response to high temperature is very similar to that of pea aphid.…”
Section: May 1980mentioning
confidence: 99%
“…However, this delicate balance can be disrupted by climate change. Among the pioneering works on the effects of weather in entomology were those of Messenger (1964Messenger ( , 1968, while a recent review of climate change on plant diseases is that of Coakley et al (1999). In their edited volume, Reddy and Hodges (2001) review many aspects of current thinking on the effects of climate change in agriculture.…”
Section: Introductionmentioning
confidence: 99%